Artificial Intelligence Personalized Marketing Content and Consumer Behavior in Nigerian SMEs - Okwudiri Nnanna-Ohuonu; Nwachukwu Peter Chikwesiri; Amarachukwu Okudo; Izuka Vivian Chinwe (goodwood publishing, 2026)
Purpose: This study examined how AI-driven personalization of digital marketing content influences consumer behavior in Nigerian Small and Medium Enterprises (SMEs). Research Methodology: A Systematic Literature Review (SLR) of 30 empirical studies published between 2015 and 2025 was performed. Data were sourced from peer-reviewed journal articles, conference papers, review studies, and industry reports that specifically examined AI-driven personalized marketing tools, particularly, product recommendation systems. Results: The findings indicate that 60% of the reviewed studies reported moderate-to-high adoption of AI-driven personalized recommendation systems among digitally mature Nigerian SMEs in the retail and e-commerce sectors. Across studies, AI-enabled personalization produced an average 15.8% increase in consumer purchase intention, with a strong mean correlation (r = 0.60) between personalized product recommendations and purchase intentions. Conclusions: AI-driven personalization significantly improves marketing effectiveness and positively shapes consumer purchase intentions in Nigerian SMEs. Limitations: The exclusive use of secondary data and SLR-based synthesis limits the generalizability and real-time assessment of AI adoption and its impact on consumer behavior. Contributions: This study consolidates empirical evidence on AI-personalized marketing in Nigerian SMEs, highlighting its impact on consumer purchase intention, while underscoring the need to address adoption barriers and ensure ethical data practices.